A study on speech rate as a prosodic feature in spontaneous narrative - Oliveira Júnior, Miguel (ALFA: Revista de Linguística, 2012)
Speech rate is examined in this paper as a prosodic feature employed in thesignaling of spontaneous narrative structure. Assuming that narratives have a structural systemin itself, and that interactants mark their moves and their more global activities in order to makethem unambiguous (JEFFERSON, 1978; SACKS, 1972), the present paper examines speech ratephenomena, from an acoustic-experimental approach, in 17 spontaneous narratives, usingone of the most influential models for narrative analysis - the Labovian Evaluative Model(LABOV, 1972) - as framework for the analysis. The prosodic variable under investigation isanalyzed on two different levels: at specific points in the narratives corresponding to sectionboundaries (local level), and within different sections in the narratives as a whole (global level).The results indicate that speech rate operates exclusively on the global level, by generating acyclical pattern of varying rates corresponding to the individual, linear sections that make upnarrative texts. Speech rate does not characterize narrative sections and is not manipulatedon the local level in order to mark narrative boundaries.